2023
DOI: 10.1371/journal.ppat.1011293
|View full text |Cite
|
Sign up to set email alerts
|

Syrian hamster convalescence from prototype SARS-CoV-2 confers measurable protection against the attenuated disease caused by the Omicron variant

Abstract: The mutation profile of the SARS-CoV-2 Omicron (lineage BA.1) variant posed a concern for naturally acquired and vaccine-induced immunity. We investigated the ability of prior infection with an early SARS-CoV-2 ancestral isolate (Australia/VIC01/2020, VIC01) to protect against disease caused by BA.1. We established that BA.1 infection in naïve Syrian hamsters resulted in a less severe disease than a comparable dose of the ancestral virus, with fewer clinical signs including less weight loss. We present data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Fold-changes against subsequent variants tested are presented as relative to the virus used for infection (Figure 4). Data for hamsters infected with ancestral, BA.1, BA.4 and BA.5.2.1 are described previously but also presented here [27,28]. As our results from the human data indicated that the FCS substitution in the BA.2.86 -A virus did not affect neutralisation titres, repeat assays with these volume-limited sera were not performed with the second virus.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Fold-changes against subsequent variants tested are presented as relative to the virus used for infection (Figure 4). Data for hamsters infected with ancestral, BA.1, BA.4 and BA.5.2.1 are described previously but also presented here [27,28]. As our results from the human data indicated that the FCS substitution in the BA.2.86 -A virus did not affect neutralisation titres, repeat assays with these volume-limited sera were not performed with the second virus.…”
Section: Resultsmentioning
confidence: 74%
“…Sera collected at day 27 post-infection from hamsters exposed to ancestral virus (n=6) and BA.1 (n=5) or day 28 post-infection with BA.4 (n=6) and BA.5.2.1 (n=6). These hamster sera were generated as previously described [27, 28]. Sera was collected from hamsters infected with XBB1.16 and XBB.2.3 (n=6 per variant) with a target dose of 1×10 4 FFU/200 µL via intranasal instillation (method previously described [27, 28]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SARS-CoV-2 variants were isolated and propagated on Vero/hSLAM cells (ECACC 04091501) before being subjected to quality control checks as previously described ( (Coombes, Bewley, Le Duff, Hurley, et al 2023). Briefly, titrations were performed using a focus-forming assay with immunostaining for nucleocapsid to visualize foci (Ryan et al 2023). Sighting for each variant into the Focus Reduction neutralization Test (FRNT) to calculate dilution at which a median of 130 foci could be counted in non-neutralized control wells was performed.…”
Section: Vdec (Uk) -Vaccine Development and Evaluation Centrementioning
confidence: 99%